2014
DOI: 10.3892/mco.2014.279
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum human epididymis protein 4 and carbohydrate antigen 125 as markers in ovarian cancer: A meta-analysis

Abstract: Abstract. Ovarian cancer (OC) is the third most common type of gynecological cancer. Measurements of human epididymis protein 4 (HE4) levels have been suggested for improving the specificity of the laboratory identification of OC. For this meta-analysis, the Medline, Embase and Cochrane databases were searched to identify relevant studies. All the included studies for diagnostic performance were combined with sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 33 publications
(18 reference statements)
6
48
1
Order By: Relevance
“…Recently, Zhen et al, conducted a meta-analysis of the available evidence on the diagnostic accuracy of HE4 and CA125. They reported that HE4 appears to be superior to CA125 regarding diagnostic accuracy in distinguishing ovarian cancer from other benign gynecological diseases (Zhen et al, 2014). Conversely, in other studies Van Gorp et al, 2011;Li et al, 2012), it has been indicated that HE4 did not perform significantly better than CA125 in the diagnosis of ovarian cancer.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Recently, Zhen et al, conducted a meta-analysis of the available evidence on the diagnostic accuracy of HE4 and CA125. They reported that HE4 appears to be superior to CA125 regarding diagnostic accuracy in distinguishing ovarian cancer from other benign gynecological diseases (Zhen et al, 2014). Conversely, in other studies Van Gorp et al, 2011;Li et al, 2012), it has been indicated that HE4 did not perform significantly better than CA125 in the diagnosis of ovarian cancer.…”
Section: Discussionmentioning
confidence: 86%
“…These findings make it reasonable that the combination improved CA125 but not HE4 performance. DOI:http://dx.doi.org/10.7314/APJCP.2016.17.1.323 Tissue CA125 and HE4 Gene Expression Offers Superior Accuracy in Discriminating Benign from Malignant Pelvic Masses Several studies (Moore et al, 2008;Huhtinen et al, 2009;Moore et al, 2009;Escudero et al, 2011;Lenhard et al, 2011;Freydanck et al, 2012;Zhen et al, 2014) reported that the combination of serum HE4 with serum CA125 further enhanced the diagnostic accuracy when compared with either maker alone, suggesting that when used in combination, the two markers HE4 and CA125 complement each other, as each improves the discriminatory performance of the other. On the contrary, Jacob et al, suggested that no benefit from combining HE4 and CA125 in the clinical setting (Jacob et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, Hellstrom et al reported the potential role of HE4 as a secreted biomarker (22), after which time serum HE4 was investigated as a possible valuable biomarker for ovarian and endometrial cancers. In a meta-analysis, Zhen et al reported that the diagnostic accuracy of HE4 in distinguishing ovarian cancer from other benign gynecological diseases was found to be superior to that of CA125 (23). More recently, Brennan et al reported in a large population-based study that serum HE4 may be a useful prognostic biomarker in endometrial cancer (17).…”
Section: Discussionmentioning
confidence: 99%
“…A second prospective trial of 472 patients showed that ROMA had a sensitivity for detecting ovarian cancer of 92.3% in post-menopausal women and 100% in premenopausal women, with an overall sensitivity of 93.8% and NPV of 99.0% [12]. There have also been multiple clinical trials worldwide validating ROMA as a diagnostic tool in differentiating benign and malignant adnexal masses [16-20]. …”
Section: Discussionmentioning
confidence: 99%